The Role of Bhabinkamtibmas in Preventing Theft Crimes With A Warning in Bantul Police - Mahendra Duta Bhaskara (Advances in Police Science Research Journal, 2021)
This research’s background is derived from researcher’s observasion in Bantul that the theft cases are increasing in these three years. These numbers is dominated by aggravated theft with 434 total cases. Researcher then observes how Bhabinkamtibmas must act with their functions, these are preemtive, preventive, and repressive. This research is conducted with qualitative model research, with analytic descriptive method. The source of this research is interview, observation, and documentation study. The result of this research is that the role of Bhabinkamtibmas is not optimal yet, there are still Bhabinkamtibmas personnel who are concurrent in two villages so that some planned activities are not optimal. The second result of research is that the optimization of the role of Bhabinkamtibmas using management functions has been implemented, but in the planning function there are still weaknesses, namely the discovery of Bhabinkamtibmas which do not have the supporting quality competencies. The third research result is that there are obstacles in the implementation of Bhabinkamtibmas duties, namely the lack of quantity and quality of personnel and infrastructure. The research suggestions are: 1) The Bantul police service unit adds personnel and infrastructure in order to maximize the role of bhabinkamtibmas which can be strengthened with elements of management so that the role of bhabinkamtibmas in preventing criminal acts of theft by means of maximum weighting can; 2) Optimizing the role of Bhabinkamtibmas by implementing management stages, namely planning, organizing, implementing, and evaluating; and 3) Improve the facilities and infrastructure of Bhabinkamtibmas Bantul Police. This is done to increase the mobility of the personnel in carrying out their duties. This facility and infrastructure factor can be used to improve the quality of personnel in terms of transportation and communication.